Antecedents and Consequences of Creativity in Product Innovation Teams1. Issue 1 (31st May 2012) - Im, Subin; Montoya, Mitzi M.; Workman, John P.
<x xml:space="preserve">Abstract</x> The generation of creative ideas and their manifestation as new products (NPs) are fundamental innovation activities of product innovation teams. Despite the importance of generating creative ideas at the fuzzy front end of the product innovation process, our understanding of antecedents and consequences of creativity of product innovation teams is limited. Drawing on Shane and Ulrich's organization design perspective of innovation, this study aims at examining the intermediary role of creativity as a critical link between team dynamics and product competitive advantage. In this study, the authors focus on NP and marketing program (MP) creativity in product innovation teams. They develop and empirically test a model that examines how internal and external team dynamics influence NP and MP creativity, and how NP and MP creativity affect product competitive advantage as a strategic innovation outcome. The study uses 206 matched responses from senior managers and product team leaders in high‐tech manufacturing firms in the United States to avoid common‐method bias. The authors use maximum likelihood estimation in a structural equation model to empirically test the proposed model. They find that two separate dimensions of creativity—novelty and meaningfulness—are differentially affected by team dynamics. For example, NP novelty as a result of divergent process is predominantly influenced by external team factors such as market‐based reward system and planning process formalization. On the other hand, NP meaningfulness as a result of convergent process is dominantly influenced by internal team factors such as social cohesion and superordinate identity. In addition, MP novelty is determined by social cohesion, superordinate identity, planning process formalization, and encouragement to take risks, while MP meaningfulness is influenced by social cohesion and planning process formalization. Our findings also suggest that NP novelty and meaningfulness, but not MP novelty and meaningfulness, play important intermediary roles in determining product competitive advantage. This study contributes to narrowing the important gap in the literature by examining the effect of team dynamics on creativity and by linking creativity to strategic innovation outcomes. Our study suggests that a firm's ability to manage team dynamics toward generating creative NPs and MPs constitutes a dynamic capability that can provide a competitive advantage over the competition.